2015
DOI: 10.1021/acs.biochem.5b00625
|View full text |Cite
|
Sign up to set email alerts
|

Catalytically Important Residues of E6AP Ubiquitin Ligase Identified Using Acid-Cleavable Photo-Cross-Linkers

Abstract: Inactivation of the E6AP E3 ubiquitin ligase (UBE3A gene) causes Angelman syndrome, while aberrant degradation of p53 by E6AP is implicated in cervical cancers. Herein, we describe the development of photo-cross-linkers to discover catalytic residues of E6AP. Using these cross-linkers, we identified covalent modifications of the E6AP catalytic cysteine and two lysines: Lys847 and Lys799. Lys847 is required for the formation of Lys48-linked polyubiquitin chains, while the K799A E6AP mutant was more active at pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…they are selective for side-chain primary amines or sulfhydryls, which are not necessarily close to relevant binding surfaces. Recently, however, new crosslinking reagents that are highly reactive and relatively nonspecific have proven useful in proteinprotein interaction studies and show promise for protein structure mapping (17,18).…”
Section: Significancementioning
confidence: 99%
“…they are selective for side-chain primary amines or sulfhydryls, which are not necessarily close to relevant binding surfaces. Recently, however, new crosslinking reagents that are highly reactive and relatively nonspecific have proven useful in proteinprotein interaction studies and show promise for protein structure mapping (17,18).…”
Section: Significancementioning
confidence: 99%
“…Moreover, amine-specific linkers with different reactive groups and spacer distances were utilized to dissect the flexible or disordered interfaces of macromolecular complexes such as MICAL3, ELKS, and Rab8A; SLAIN2, CLASP2, and ch-TOG (Liu et al, 2017); NLRP1 and DPP9 (Hollingsworth et al, 2021); Rpn2 and Rpn13 (Gong et al, 2020). Recent developments in linker chemistry have produced crosslinker reagents that are cleavable, photo-activatable, or heterobifunctional, permitting controlled crosslink reactions, low background, improved sensitivity (Beard et al, 2021;Krist and Statsyuk 2015), and even in a native cellular environment (Xie et al, 2021). For instance, a crosslinker bearing a photoreactive moiety as well as a reducible spacer have been developed.…”
Section: Interfaces Revealed By a Chemical Crosslinker Coupled To Msmentioning
confidence: 99%
“…The utility of photocrosslinker incorporation into E2s for E3 study has also been demonstrated. Crosslinker incorporation by chemical labeling has enabled the mapping of Cys E3 catalytic residues (Krist and Statsyuk, 2015) and, more recently, incorporation into an E2 by chemical synthesis has been used to generate a photoaffinity probe for a SUMO E3 (Zhang et al, 2019). However, the utility of these technologies as ABPs has not been demonstrated.…”
Section: Introductionmentioning
confidence: 99%